2009
DOI: 10.1159/000264634
|View full text |Cite
|
Sign up to set email alerts
|

An Oral Sorbent, AST-120, Increases Klotho Expression and Inhibits Cell Senescence in the Kidney of Uremic Rats

Abstract: Background/Aim: Klotho, an anti-aging gene, is primarily expressed in the kidney, and its renal expression is decreased in chronic renal failure (CRF). We determined if administration of an oral sorbent, AST-120, increases the expression of Klotho, and inhibits cell senescence in the kidney of CRF rats. Methods: CRF rats were produced by 4/5-nephrectomy. AST-120 was administered to the CRF rats at a dose of 4 g/kg with powder chow for 16 weeks, whereas powder chow alone was administered to control CRF rats. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 32 publications
0
32
0
1
Order By: Relevance
“…In some studies with patients with CKD, AST-120 decreased serum and urinary IS levels and the levels of advanced glycation end products (AGEs) (24,25). Also, AST-120 increased the renal expression of Klotho, which was decreased in uremic condition and inhibited cell senescence in the kidney of uremic rats, probably by alleviating IS overload on the kidney (26).…”
Section: Discussionmentioning
confidence: 92%
“…In some studies with patients with CKD, AST-120 decreased serum and urinary IS levels and the levels of advanced glycation end products (AGEs) (24,25). Also, AST-120 increased the renal expression of Klotho, which was decreased in uremic condition and inhibited cell senescence in the kidney of uremic rats, probably by alleviating IS overload on the kidney (26).…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, a study by Adijiang and Niwa demonstrated that administration of AST-120 preserves renal expression of Klotho and prevents tubular cell senescence in the kidneys of chronic renal failure (CRF) rats [Adijiang and Niwa, 2010]. A decreased expression of Klotho, a protein predominantly expressed in mouse, rat and human kidneys, may play an important role in vascular calcification, arteriosclerosis and osteoporosis development.…”
Section: Ast-120 In Cvdsmentioning
confidence: 99%
“…We demonstrated that administration of AST-120 to CKD rats significantly increased the expression of Klotho in the kidney as compared with CKD rats [20]. Recently, we reported that indoxyl sulfate administration reduced immunostaining intensity of Klotho in rat kidneys [21].…”
Section: Introductionmentioning
confidence: 99%